FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN KONTRASEPSI SUNTIK DEPO MEDROXY PROGESTERONE ACETATE (DMPA) DI PUSKESMAS MERAL KABUPATEN KARIMUN - Sihombing, Jenny Uli Arta; Sulistyawati, Tri Ribut (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Indonesia is a country recognized as the fourth biggest population in the world with 258,316,051 inhabitants. For the attempt to control the birth rate of the baby, Indonesian government implements a Family Planning program using various methods of contraception such as Depo Medroxy Progesterone Acetate (DMPA) injectable contraception that is often used by childbearing age couple. This study aims to determine promising factors associated with the use Depo Medroxy Progesterone Acetate (DMPA) contraception method particularly at Meral Health Centre of Karimun in 2018, namely factors of woman’s age and knowledge, as well as husband’s support. This research is an analytical survey with a cross sectional approach conducted from May to July 2018 with 99 respondents selected through simple random sampling technique. The research instrument used was questionnaires, then further analyzed by chi square statistical test. The result reveals a correlation between factor of wife’s age with the use of DMPA contraception with the p value = 0.007 <0.05, besides it is also noted a correlation between wife’s knowledge with the use of DMPA contraception with p value = 0.017 <0.05, and a correlation between husband’s support with the use of DMPA injectable contraception with p value = 0.023 <0.05. From the findings, it can be concluded that there is a significant correlation between woman’s age and knowledge also support of husband with the use of DMPA injectable contraception at Meral Health Center of Kamrimun in 2018. Finally, it is hoped that midwives as the medical personnel to develop both family planning information and services in form of counseling and assistance about contraceptive methods to be use by the participants.